Forensic medicine & toxicology - Aggarwal, Gaurav (Smart Study Series, 2009)
This volume on forensic medicine and toxicology from Smart Study Series acts as an exam preparatory book that deepens understanding of concepts in forensic medicine and toxicology. It provides MCQs of major OG entrance exams of India with answers and explainations.